The long path of penalty: from the debate on abolition of the capital penalty to life imprisonment. The Italian case of life imprisonment - Mazzuca, Jessica (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This paper analyses the problematic relationship between death penalty and life imprisonment. The first part of the work examines the main steps that led to the replacement of capital punishment with life imprisonment. A topic that calls into question a comparative evaluation between the utilitarian conception of Cesare Beccaria and the thesis of Kant and Hegel in favor of capital punishment. From the basis of these assumptions, we proceeded to analyse the more recent institution of life imprisonment, by means of which the State takes the life of the condemned man,  without taking it away from him physically, but socially.
Keywords: death penalty; life imprisonment and re-education; social reintegration; purpose of punishment